RETRACTED: Case Report: Treatment of Hypertrophic Cardiomyopathy With Stereotactic Body Radiotherapy - Xiao, Longzihui; Liu, Jiayi; Zhang, Yingzhe; Liu, Yuefei; Tang, Yan; Zhang, Minping; Ding, Zhuyuan; Xiao, Enhua; Chen, Taili (Frontiers in Medicine, 2022)
Patients with hypertrophic cardiomyopathy (HCM), which is characterized by left ventricular hypertrophy, is usually treated with medications such as calcium channel blockers or beta-blockers and invasive treatments such as transcatheter alcohol septal ablation, percutaneous radiofrequency ablation, or heart transplantation. However, non-invasive methods have not been employed for the management of patients with HCM. A 71-year-old male who presented with occasional chest pain for approximately 2 months and had been diagnosed with HCM since he was 39 years old due to occasional fainting was treated with a novel method for HCM using stereotactic body radiotherapy (SBRT). The administration of 25 Gy of radiation as one fraction led to an improvement in his quality of life. No toxicity occurred during or immediately after the treatment. Our observations suggest that SBRT may be a reasonable treatment approach for patients with HCM who are not suitable for surgery.